Fostering university-community engagement in Malaysia. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2012)
Universities have traditionally functioned as institutions of higher learning devoted to the search and discovery of knowledge and truth. For the university, the development of knowledge is made through research, which is transmitted through the process of teaching and learning.